ArcGeomorphometry: A toolbox for geomorphometric characterisation of DEMs in the ArcGIS environment. (December 2015) - Rigol-Sanchez, Juan P.; Stuart, Neil; Pulido-Bosch, Antonio
Abstract: A software tool is described for the extraction of geomorphometric land surface variables and features from Digital Elevation Models (DEMs). The ArcGeomorphometry Toolbox consists of a series of Python/Numpy processing functions, presented through an easy-to-use graphical menu for the widely used ArcGIS package. Although many GIS provide some operations for analysing DEMs, the methods are often only partially implemented and can be difficult to find and used effectively. Since the results of automated characterisation of landscapes from DEMs are influenced by the extent being considered, the resolution of the source DEM and the size of the kernel (analysis window) used for processing, we have developed a tool to allow GIS users to flexibly apply several multi-scale analysis methods to parameterise and classify a DEM into discrete land surface units. Users can control the threshold values for land surface classifications. The size of the processing kernel can be used to identify land surface features across a range of landscape scales. The pattern of land surface units from each attempt at classification is displayed immediately and can then be processed in the GIS alongside additional data that can assist with a visual assessment and comparison of a series of results. The functionality of the ArcGeomorphometry toolbox is described using an example DEM. Highlights: A software tool for geomorphometric analysis of DEMs within GIS is implemented. Operations consist of a series of Python/Numpy processing functions. Operations are presented through an easy-to-use graphical menu. It allows GIS users to apply several multi-scale analysis and classification methods.